2013
DOI: 10.5194/angeo-31-319-2013
|View full text |Cite
|
Sign up to set email alerts
|

Magnetosheath dynamic pressure enhancements: occurrence and typical properties

Abstract: The first comprehensive statistical study of large-amplitude (> 100%) transient enhancements of the magnetosheath dynamic pressure reveals events of up to ~ 15 times the ambient dynamic pressure with durations up to 3 min and an average duration of around 30 s, predominantly downstream of the quasi-parallel shock. The dynamic pressure transients are most often dominated by velocity increases along with a small fractional increase in the density, though the velocity is generally only deflected by a few d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

38
206
2
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(251 citation statements)
references
References 43 publications
(108 reference statements)
38
206
2
5
Order By: Relevance
“…High-speed jets in the magnetosheath studied by Plaschke et al [2013] were observed behind the quasi-perpendicular bow shock or the foreshock region upstream and during radial IMF orientation with an average duration of around 30 s. These findings are consistent with the bow shock ripple based generation mechanism suggested by Hietala et al [2009]. The dynamic pressure transients in the magnetosheath containing increases in the density reported by Archer and Horbury [2013] exhibit similar properties.…”
Section: Introductionsupporting
confidence: 72%
“…High-speed jets in the magnetosheath studied by Plaschke et al [2013] were observed behind the quasi-perpendicular bow shock or the foreshock region upstream and during radial IMF orientation with an average duration of around 30 s. These findings are consistent with the bow shock ripple based generation mechanism suggested by Hietala et al [2009]. The dynamic pressure transients in the magnetosheath containing increases in the density reported by Archer and Horbury [2013] exhibit similar properties.…”
Section: Introductionsupporting
confidence: 72%
“…To complicate matters, the means of transporting mass, momentum and energy across the magnetopause involves a synthesis of magnetohydrodynamic (MHD), kinetic, and numerous wave-particle interaction processes. In spite of that, several candidates capable of facilitating transport across the magnetopause have been identified: magnetic reconnection (Dungey, 1961), impulsive penetration (Karlsson et al, 2012;Archer and Horbury, 2013;Plaschke et al, 2013), Kinetic Alfvén waves (Johnson and Cheng, 1997;Chaston et al, 2008) the Kelvin Helmholtz Instability (KHI) (Miura and Pritchett, 1982;Miura, 1992;Chen et al, 1997;Otto and Fairfield, 2000;Nykyri and Otto, 2001;Nykyri et al, 2006;Hasegawa et al, 2009) and flux transfer events (Russell and Elphic, 1978). It is noteworthy that each of these processes do not strictly operate independently, and during certain conditions, plasma transport may be a result of a combination of these processes operating simultaneously.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…In particular, the magnetosheath region downstream of the quasi-parallel shock is permeated by magnetosheath jets. Correspondingly, subsolar jet occurrence is found to be controlled -almost exclusively -by the cone angle of the interplanetary magnetic field (IMF), i.e., the angle between the IMF and the EarthSun line, while other solar wind parameters or their variability only play a minor role (Archer et al, 2012;Archer and Horbury, 2013;Plaschke et al, 2013). A substantial fraction of jets is believed to originate from bow shock ripples or undulations , which are common at the reforming, patchy, quasi-parallel bow shock (Schwartz and Burgess, 1991;Omidi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%